Secular Trends in the Burden of Multiple Myeloma From 1990 to 2019 and Its Projection Until 2044 in China - Yumei Zhao; Yumei Zhao; Dongdong Niu; Enlin Ye; Jiasheng Huang; Jia Wang; Xuefei Hou; Xuefei Hou; Jiayuan Wu; Jiayuan Wu (Frontiers Media S.A., 2022)
ObjectiveMultiple myeloma (MM) imposes a heavy burden in China. Understanding the secular trend of MM burden and projecting its future trend could facilitate appropriate public health planning and improve the management of MM.MethodsSex-specific incidence and mortality rates of MM in China from 1990 to 2019 were collected from the Global Burden of Disease 2019 study. The secular trend of MM burden was analyzed by joinpoint regression. Age-period-cohort model was used to analyze the effects of age, period, and birth cohort on MM burden and project future trends up to 2044.ResultsFrom 1990 to 2019, the age-standardized incidence and mortality rates of MM continued to increase in males. For females, the age-standardized rates were stable in MM incidence and decreased in MM mortality. Males had a higher disease burden of MM than females. Age effects were the most significant risk factor for MM incidence and mortality. Moreover, the risk of MM incidence and mortality increased with increasing time period but decreased with birth cohort in males and females. The age-standardized incidence and mortality rates of MM in China is predicted to be continuously increasing over the next 25 years.ConclusionThe burden of MM in China is expected to continue to increase in the future, with significant sex difference. A comprehensive understanding of the risk characteristics and disease pattern of MM could help develop timely intervention measures to effectively reduce its burden.